The Meanings of Racist and Sexist Trash Talk for Men of Color: A Cultural Sociological Approach to Studying Gaming Culture - Ortiz, Stephanie M (New Media & Society, 2019)
Scholars have documented how people of color experience gaming culture as violent, yet it is unclear how this violence shapes conceptualizations of gaming culture. Undertaking a cultural sociological approach that foregrounds meaning-making, I demonstrate that trash talk is a useful site to explore how social actors construct and negotiate gaming culture. Analyzing data from 12 qualitative interviews with men of color, I argue that trash talk is a practice of boundary-making that reproduces racism and sexism. Respondent narratives about gaming culture vis-à-vis trash talk thus show how gaming culture is socially constructed in everyday interactions, and bound to cultural repertoires and structural conditions that exist outside of gaming. This study provides a potential avenue to explore the socially constructed and dynamic nature of gaming culture and gamer identity.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Étude de la réception; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé